2002
DOI: 10.1021/jp025858k
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic Properties of Aqueous Ionene Solutions

Abstract: Osmotic coefficients of aqueous solutions of 3,3-, 4,5-, 6,6-, and 6,9-ionenes with bromide and chloride counterions were measured at 298 K and in the concentration range from 0.001 to 0.1 mol/dm3. The measured osmotic coefficients are very low, indicating large deviations from ideality caused by strong interactions in these systems. The solutions with chloride counterions have a higher osmotic coefficient than the corresponding bromide solutions, which is in agreement with experimental data for the counterion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
81
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(96 citation statements)
references
References 42 publications
14
81
1
Order By: Relevance
“…These measurements indicate strong deviations from theoretical predictions based on the continuumsolvent models [3,4,14] of a polyelectrolyte solution. For example, the measured activity and osmotic coefficients are much lower than theoretically predicted [32,35], and the deviations are stronger for more hydrophobic 6,6 and 6,9 ionenes. The osmotic coefficients of ionene solutions with Br -ions as counterions were slightly (but significantly beyond the range of experimental uncertainty) lower than the corresponding chloride solutions.…”
Section: Osmotic Coefficientmentioning
confidence: 70%
See 1 more Smart Citation
“…These measurements indicate strong deviations from theoretical predictions based on the continuumsolvent models [3,4,14] of a polyelectrolyte solution. For example, the measured activity and osmotic coefficients are much lower than theoretically predicted [32,35], and the deviations are stronger for more hydrophobic 6,6 and 6,9 ionenes. The osmotic coefficients of ionene solutions with Br -ions as counterions were slightly (but significantly beyond the range of experimental uncertainty) lower than the corresponding chloride solutions.…”
Section: Osmotic Coefficientmentioning
confidence: 70%
“…In addition, they are excellent materials for studying the effects of polyion charge density and hydrophobicity on physicochemical properties. Ionene solutions have been characterized experimentally in several papers: Minakata and coworkers [32][33][34] measured the conductance and activity coefficients of 3,3; 4,5; 6,6; and 6,9 ionene solutions, while heats of dilution and osmotic coefficients were determined by Pohar and coworkers [13,35]. These measurements indicate strong deviations from theoretical predictions based on the continuumsolvent models [3,4,14] of a polyelectrolyte solution.…”
Section: Osmotic Coefficientmentioning
confidence: 99%
“…Recently, it was shown by chromatography that the molecular mass of 3,3-and 6,6-ionene bromides was 37 and 30 kDa, respectively [46]. The polyelectrolytic character of x, y-ionene solutions was previously confirmed by osmotic coefficient data [22], by small angle neutron scattering (SANS) experiments [47], as well as by viscosity [48,49] and conductivity measurements [25,29,44].…”
Section: Experimental Partmentioning
confidence: 98%
“…The interplay between the hydrophobicity of ionenes and specific ion effects was presented in a series of papers published by our [22][23][24][25][26][27][28][29] and other groups [30][31][32]. It was shown that aqueous ionene solutions exhibit strong specific ion effects, where replacing one counterion species by another may yield qualitatively different behaviour of the solution.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the classical Poisson-Boltzmann ͑PB͒ theory, 1,5,6 formal statistical mechanical approaches such as the hypernetted chain/mean spherical approximation ͑HNC/MSA͒, 13,14 the PB/MSA, 15 and the modified PB ͑MPB͒ theory [16][17][18][19] have been utilized in conjunction with the cylindrical cell model. The theoretical efforts have been supplemented by numerical computer simulations, viz., with parameters corresponding to DNA, [20][21][22][23][24][25][26][27][28][29][30] PSS, 31,32 ionenes, 33 and polyamines, 19 the focus being principally on polyionsimple ion correlation and the thermodynamics of the solution. The simulations suggest that the PB equation is generally semiquantitative in describing equilibrium properties for monovalent systems but is less certain for higher and/or multivalent systems.…”
Section: Introductionmentioning
confidence: 99%